A survey of medical cannabis use during perimenopause and postmenopause. Issue 9 (2nd September 2022) - Dahlgren, M. Kathryn; El-Abboud, Celine; Lambros, Ashley M.; Sagar, Kelly A.; Smith, Rosemary T.; Gruber, Staci A.
Abstract : This survey study assessed modes of cannabis use endorsed by perimenopausal and postmenopausal individuals and specific menopause-related symptoms indicated for medical cannabis use. This information will help inform next steps for clinical trials designed to assess the efficacy of specific cannabinoid-based products. Abstract: Objective: Expanding access to legal cannabis has dovetailed with increased interest in medical cannabis (MC) use; however, there is a paucity of research examining MC use to alleviate menopause-related symptoms. This survey study assessed patterns of MC use in perimenopausal and postmenopausal individuals. Methods: Participants (perimenopausal, n = 131; postmenopausal, n = 127) completed assessments of menopause-related symptomatology and cannabis use, including modes of use, type of use, and menopause-related symptoms addressed by MC use. Results: Most participants reported current cannabis use (86.1%) and endorsed using MC for menopause-related symptoms (78.7%). The most common modes of use were smoking (84.3%) and edibles (78.3%), and the top menopause-related symptoms for MC use were sleep disturbance (67.4%) and mood/anxiety (46.1%). Relative to postmenopausal participants, perimenopausal participants reported significantly worse menopause-related symptomatology on the vasomotor and psychosocial subscales of the Menopause-Specific Quality of Life Questionnaire ( P s ≤ 0.04), including greater burden of anxiety ( P = 0.01) and hot flash ( P = 0.04) symptoms. In addition, perimenopausal participants reported higher incidence of depression ( P = 0.03) and anxiety diagnoses ( P < 0.01), as well as increased use of MC to treat menopause-related mood/anxiety symptoms relative to postmenopausal participants ( P = 0.01). Conclusions: Results suggest that many individuals are currently using MC as an adjunctive treatment for menopause-related symptoms, particularly sleep disturbance and mood/anxiety. Future research should examine the impact of different MC use characteristics (e.g., cannabinoid profiles) on the efficacy of MC use for menopause-related symptoms. Increased severity and prevalence of mood and anxiety symptoms in perimenopausal participants suggest promising targets for clinical trials of cannabinoid-based therapies.